shRNA-interfered of Nrf2 reveals a critical role for Keap1-Nrf2 signaling pathway during effects of zearalenone induced oxidative stress in IPEC-J2 cells - Qun Cheng; Shu Zhen Jiang; Li Bo Huang; Wei Ren Yang (Animal Bioscience)
Objective This study aims to verify the protective effect of the Kelch-like ECH-associated protein1 (Keap1)–nuclear factor erythroid 2–related factor 2 (Nrf2) signaling pathways by studying the effect of plasmids containing Nrf2–small hairpin RNA (shRNA) interference down-regulation of Nrf2 on zearalenone (ZEA)–induced intestinal porcine epithelial cells (IPEC-J2) oxidative stress. Methods We constructed an IPEC-J2 model that interferes with Nrf2 expression, set blank (control), negative control group (Sh-control), positive control group (Sh-Nrf2), and added 10, 20, and 40 μmol/L ZEA experimental group (Sh-Nrf2+ZEA10, Sh-Nrf2+ZEA20, and Sh-Nrf2+ZEA40). Results The study results showed that, compared with the Sh-Nrf2 group, ZEA significantly increased the apoptosis rate of IPEC-J2 in a time- and dose-dependent manner. Compared with the Sh-Nrf2 group, the activities of total superoxide dismutase and glutathione peroxidase and relative expressions of Keap1 at mRNA and protein level in the Sh-Nrf2+ZEA20 and Sh-Nrf2+ZEA40 groups were significantly reduced, the malondialdehyde level, and the fluorescence intensity around and within the nucleus of reactive oxygen species and Nrf2, and the relative expressions of Nrf2, quinone oxidoreductase 1, and hemeoxygenase 1 at mRNA and protein level significantly increased. Conclusion These results further prove that interfering with the expression of Nrf2 in IPEC-J2 cells affected the activation of the Keap1-Nrf2 signaling pathway and reduced the ability of cells to resist ZEA-induced oxidative stress. Therefore, the Keap1-Nrf2 signaling pathway had an important protective effect in ZEA-induced intestinal oxidative stress.